Mapping the Intellectual Landscape of Collaborative Educational Supervision: A Bibliometric Review - Rika Yosepa; Aan Komariah; Djam’an Satori; Nugraha Suharto (Universitas Negeri Malang, 2025)
Abstract: This study aims to map the intellectual landscape, thematic development, and research gaps in collaborative educational supervision through a bibliometric review of Scopus-indexed literature. Collaborative supervision has increasingly been discussed as an alternative to traditional hierarchical supervision because it emphasizes dialogue, shared responsibility, reflective inquiry, and professional learning. However, the development of this topic remains conceptually fragmented and has not been sufficiently mapped as a coherent field of educational research. This study employed a bibliometric analysis integrated with a narrative literature review. Data were collected from the Scopus database using the keywords “collaborative supervision” and “education” in the title, abstract, and keyword fields. After applying inclusion and exclusion criteria, 27 relevant documents published between 2000 and 2024 were analyzed. Bibliometric mapping was conducted using VOSviewer and Bibliometrix to examine publication trends, institutional and geographical contributions, keyword co-occurrence, and thematic structures, while the narrative review was used to interpret the conceptual and practical meanings of the most relevant studies. The findings show that scholarly attention to collaborative supervision has grown gradually since the early 2000s, with stronger development after the 2010s and publication peaks in 2003, 2015, and 2024. The United States appears as the most productive country, while institutional contributions remain dispersed, indicating that no single academic center dominates this field. Keyword analysis reveals several thematic clusters, including health professions education, clinical and fieldwork supervision, collaborative learning, teacher development, and professional identity formation. These findings indicate that collaborative supervision is an interdisciplinary concept applied across teacher education, higher education, social work, medical education, and allied health training. Nevertheless, the field still faces challenges related to inconsistent definitions, limited empirical validation, and underrepresentation of Global South contexts. The study concludes that collaborative supervision has strong potential to support professional development and sustainable educational improvement, but future research should develop clearer theoretical frameworks, expand comparative and longitudinal studies, and explore digital or hybrid supervision models. Keywords: collaborative supervision, educational supervision, teacher development, bibliometric analysis, professional learning